KONSTRIBUSI OSIS DALAM MEMBENTUK KARAKTER TEMAN SEBAYA - Muhajir (FITRAH: International Islamic Education Journal, 2021)
The OSIS supervisor is usually appointed by the school to assist the OSIS management in carrying out their duties and the principal is the main person in charge of OSIS activities. In terms of funding, all OSIS activities are funded from the School Revenue and Expenditure Budget (APBS). Sometimes in the field, OSIS activities often experience obstacles, for example the emergence of violations committed by OSIS administrators who are not orderly when participating in routine coaching. As for the title of this research is "Management of Student Council Development in Shaping Peer Character at MTsN 9 Senuddon North Aceh". The type of research used in this study is qualitative research, namely research procedures that produce descriptive data in the form of written and spoken words from people who observe. Based on the results of the study, it can be concluded that the management of OSIS development in shaping the character of peers at MTsN 9 Senuddon Aceh Utara is a value inculcation approach, a cognitive development approach, a value clarification approach and an action learning approach. The obstacles to OSIS development in shaping the character of students at MTsN 9 Senuddon Aceh Utara are the lack of student interest in organizing and limited time.